Sustainability Goal and Women Empowerment through Women Education and Microcredit Facility in Pakistan - Mushtaq, Muhammad; Din, Badariah Haji (International Journal of Economics and Financial Issues, 2025)
The purpose of the study is to explore the objective such as Sustainability goals and women empowerment through women education and women empowerment’s role in country development. To attain the objective of the study, we used the primary data through questionnaire collected from women located in Pakistan that attain the micro-credit facility. The Smart Partial least squares (PLS) method is used as method of estimation in the study. Our findings show that microfinance credit services have significant positive relationship with women empowerment. The microfinance credit services have significant positive relationship with women education. The women education has significant positive relationship with women empowerment. Moreover, our results indicating the significant positive mediating relationship of women education. We concluded that the microfinance credit along with education improve the women empowerment because the education is the integral part to decide the investment decision accurately that boost the women empowerment with credit facility. Moreover, this study advocated the significant implications for investors, government and legislators to improve the women empowerment in the country that leads to economic development. Investors make investment in microcredit to facilitate the women through education and can protect the investment with secure repayment pattern.